Answer:
f(-2) = 4
f(0.5)= 0
f(1)=1
Step-by-step explanation:
Answer:
33/4
Step-by-step explanation:
Let the first number be x, and the second number be y.
x - y = 4
x + y = -7
Solve for x in the first equation.
x - y = 4
x = 4 + y
Put x as (4 + y) in the second equation and solve for y.
4 + y + y = -7
4 + 2y = -7
2y = -7 - 4
2y = -11
y = -11/2
Put y as -11/2 in the first equation and solve for x.
x - y = 4
x - (-11/2) = 4
x + 11/2 = 4
x = 4 - 11/2
x = -3/2
Their product is:
-11/2 × -3/2
33/4
Answer:
4:1 or 4/1
Step-by-step explanation:
Original surface area: Each side is 1 * 1 = 1 and there are 6 sides, so 1 * 6 = 6.
New surface area: Each side is 2*2 = 4, and there are 6 sides, so 4 * 6 = 24
The ratio would be 24:6, or 4:1. As a fraction, this would be 4/1
You divide the numerator by the denominator, meaning you divide 32 by 3.